Welfare Economics: Reviving the Prophet's Business Ethics in the 21st Century - Nindy Jufriyanti; Aisyah Febria Ghita Putri; Saipul Azis; Abi Suar; Dea Adela (Journal of Islamic Economics and Finance Studies, 2026)
The economic concept in the early Islamic period was characterized by strong principles of justice, social welfare, and ethics, where economic activity was not only seen as material trade but also as a means to achieve spiritual goals. This study aims to describe the function of the economic system during the time of the Prophet Muhammad (peace be upon him) as an ideal model rooted in the values of distributive justice and demonstrate its relevance in addressing contemporary economic inequality. Using qualitative methods based on library research, data were analyzed descriptively, analytically, and comparatively through primary sources from the Qur'an and Hadith as well as relevant secondary literature. The results show that welfare economics in Islam is realized through concrete instruments such as the obligation of zakat for wealth redistribution and the prohibition of usury to prevent exploitation. The transformation from a system focused on the accumulation of personal gain in Mecca to a socio-religious order in Medina demonstrates that the integration of ethics in business can improve income distribution and community independence. The utilization of Baitul Maal for infrastructure, education, and social services at that time provided vital inspiration for the development of modern Islamic economic policies in Indonesia that are more inclusive and stable. Thus, reviving the Prophet's business ethics in the 21st century is a strategic solution for creating an economic order based on social justice and collective responsibility.